EVALUASI KEBIJAKAN PENETAPAN KOTA SERANG SEBAGAI IBU KOTA PROVINSI BANTEN (Studi Reformasi Birokrasi Pelayanan di Kecamatan Taktakan Kota Serang) - Rethorika Berthanilla; Marthalena Marthalena; Arif Nugroho (Kolaborasi : Jurnal Administrasi Publik, 2019)
Problems such as the lack of human resources who have the competence and skills with basic public services, the low level of service, the infrastructure of the village office that is less representative, the low performance of the village chief and there are still some village programs that have not been implemented. The purpose of this study was to analyze public service bureaucratic reforms in a number of villages in the Taktakan Subdistrict of Serang City in an evaluation of the policy to determine Serang City as the Capital of Banten Province. The research method used is a qualitative approach. Data collection techniques using observation and interviews with data analysis techniques through (1) data condensation (data condensation), (2) Presentation of data (display data), (3) withdrawal of conclusions (conclusion drawing). The results showed that the bureaucratic reform of public services in several villages in the District of Taktakan, Serang in evaluating the policy to determine Serang City as the Capital of Banten Province in several aspects still needs to be evaluated comprehensively. The dimensions of public service policies, limited human resources and infrastructure, service information systems and public service policy innovations are still not optimal, even though the fulfillment of the evaluation of public service principles such as justice, participation, transparency and accountability, and empowerment and accessibility have been implemented with well.